2022
DOI: 10.1039/d1nr07772d
|View full text |Cite
|
Sign up to set email alerts
|

Metallic vs. semiconducting properties of quasi-one-dimensional tantalum selenide van der Waals nanoribbons

Abstract: We conducted a tip-enhanced Raman scattering spectroscopy (TERS) and photoluminescence (PL) study of quasi-1D TaSe3-δ nanoribbons exfoliated onto gold substrates. At a selenium deficiency of δ~0.25 (Se/Ta=2.75,), the nanoribbons exhibit...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 62 publications
(87 reference statements)
0
6
0
Order By: Relevance
“…Some selenium and iodide deficiencies are well‐known for metal chalcogenide compounds and are expected here. [ 45,46 ] The details of PXRD, SEM, EDS, and composition are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Some selenium and iodide deficiencies are well‐known for metal chalcogenide compounds and are expected here. [ 45,46 ] The details of PXRD, SEM, EDS, and composition are provided in the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Kargar et al prepared TaSe 2.75 and TaSe 2.85 NRBs, and their electrical properties were examined by tip-enhanced Raman scattering spectroscopy (TERS) and photoluminescence (PL) analysis. 597 It was revealed that TaSe 2.75 NRBs exhibited a strong broad PL peak centered at 922 nm and TERS response under 785 nm laser excitation, indicating the semiconducting behavior. In contrast, TaSe 2.85 NRBs showed neither a PL nor TERS response, which was consistent with the metallic characteristic.…”
Section: Metal-assisted Exfoliationmentioning
confidence: 97%
“…To overcome the issue, most of the research has been focused on adjusting γ MC‑Substrate . As well as the intrinsically layered 2D MCs, quasi 1D vdW NRBs that consist of atomic threads weakly bound by vdW interaction can be directly exfoliated by adhesion tape into quasi 1D NBs. Typically, bulk crystals are first synthesized by the chemical vapor transport method, then exfoliated, and transferred onto desired substrates. Geremew et al fabricated ZrTe 3 NRBs with a thickness of ∼50 nm by direct peel-off .…”
Section: Exfoliation Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[ 25 ] 1D such as semiconducting nanowires, carbon nanotubes, organic polymers, etc. [ 26 ] 2D materials, for example, TMDCs and other families of 2D materials such as MXenes. [ 27 ] 3D such as germanium, silicon carbide, etc.…”
Section: Van Der Waals (Vdws) Heterostructurementioning
confidence: 99%